The Influence of Profession Risk and Income Level on The Decision to Purchase Personal Accident Insurance Products (Case Study of Bandar Setia Kec Village Community, Percut Sei Tuan): - Gita Islya Asmara; Muhammad Arif; Nurul Jannah (ProBisnis : Jurnal Manajemen, 2023)
This study seeks to determine the impact of profession risk and income level on consumer choice of personal accident insurance products in Bandar Setia Village, Kec.  Percut Sei Tuan.  This research utilizes a quantitative approach.  Using the cluster random sampling model and subsequent random sampling, the population is collected.  By using the Slovin formula with an error rate of 10%, the population of this study amounted to 17,269 people so that the total sample was 100 people.  Descriptive statistical analysis, Partial Least Square (SEM-PLS), Outer Model, and Inner Model are the data processing methods used in this study.  The results of the research processed with SmartPls 3.2.9 Software show that Profession Risk (X1) has no effect on Purchase Decisions (Y) with the T-statistic showing a number of 0.211 <1.96 and it can also be proven that the P value is 0.839 > 0  .05.  And the level of income affects purchasing decisions with a T-statistic value indicating a range of 5,925 > 1.96 and it can also be proven by looking at the P value of 0.000 <0.05.  Based on the results of the F-Square Test for Profession Risk (X1) and Income Level (X2) which influence the purchase decision (Y) simultaneously, it can be seen that the F hit is greater than the F table, namely 48.5 > 3.09.  And the R-Square of 0.524 indicates that profession risk and income level have a simultaneous effect of 52% on buying decisions